PENDIDIKAN MULTIKULTURAL PADA PONDOK PESANTREN DI ERA MODERN - Marzuki, Sumansi; Nabilla, Sukma; Redzky, Muhammad (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Learning strategies are very useful for educators and students in learning procedures. For educators, this learning strategy serves as the basis and reference for regular activities according to the system for carrying out learning. Tolerance is an attitude and activity that respects differences, ethnicity, religion, attitudes, opinions and activities of other people besides oneself. In a society based on Pancasila, especially the first precept, piety to God is absolute according to all religions and beliefs. All religions respect people, so all religious people must respect each other. By this rule harmony is promoted between representatives of different religions. The notion that education is a means and tool for imparting knowledge not only reduces the true meaning and purpose of education, but also focuses students to create a future. True education is the development and development of human potential to have character, integrity, and meaningful competence in life. The educational model in Islamic boarding schools is regulated by a strict schedule, program of activities, procedures and strict rules. Santri are gathered in a centralized and monolithic environment (dormitory), although with rules from top to bottom. Islamic boarding schools have become a separate identity for Islamic educational institutions in Indonesia. In fact, even though they are heterogeneous in terms of ethnicity, culture and language, they can live a peaceful life and have strong emotional attitudes in maintaining loyalty and solidarity.